Cognitive engagement and academic satisfaction: critical issues related to the constructs - Rahim, Rahama; Dzulkifli, Mariam Adawiah (IIUM Press, 2024)
Research on the psychological construct of cognitive engagement and how it relates to students' academic satisfaction has been noted to have significantly increased recently. Many research findings have supported their association as indicators of academic achievement. The present paper aims to review and analyse research on cognitive engagement and academic satisfaction and to highlight the possible conceptual and methodological issues in this area of research. While numerous studies have suggested the connection between academic engagement and academic satisfaction, the specific link between cognitive engagement and academic satisfaction still needs to be explored. Even studies on academic satisfaction need to be conducted more adequately, while studies on life satisfaction and job satisfaction have drawn more attention. Moreover, scholars describe the dimensions of cognitive engagement in different ways, which may cause vagueness. In addition, more study is also essential by focusing on the relationship between cognitive engagement and academic satisfaction across different academic disciplines. Furthermore, apart from quantitative-based research, a qualitative approach can be followed to understand these constructs better. Ultimately, this paper offers some directions for future researchers to develop insight.